Effect of Gamma-irradiation on the Fatty Acid Composition of Salted, Semi-dried Vietnamese Scad and Bombay duck
Effect of gamma irradiation on the lipid and fatty acid composition of semi-dried Bombay duck (Harpodon nehcreus) and Vietnamese scad (Alepes mate) was studied. In both these dried fishes, c16:0 aand c18:1 were the predominant fatty acids and the fishes contained ignificant quantities of the n-3 polyunsaturated fatty acids (PUFAs